2008
DOI: 10.1118/1.2936220
|View full text |Cite
|
Sign up to set email alerts
|

DCEMRI of breast lesions: Is kinetic analysis equally effective for both mass and nonmass-like enhancement?

Abstract: To perform a pilot study investigating whether the sensitivity and specificity of kinetic parameters can be improved by considering mass and nonmass breast lesions separately. The contrast media uptake and washout kinetics in benign and malignant breast lesions were analyzed using an empirical mathematical model ͑EMM͒, and model parameters were compared in lesions with masslike and nonmass-like enhancement characteristics. 34 benign and 78 malignant breast lesions were selected for review. Dynamic MR protocol:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 43 publications
3
36
1
2
Order By: Relevance
“…Evaluating the enhancing patterns of focal mass lesions on dynamic study is useful in diŠeren-tiating benign and malignant lesions. [6][7][8][9][10][11] In contrast, such diŠerentiation is often di‹cult with nonmass-like enhancement because there is no standardized method of interpreting non-mass-like enhancement lesions. [6][7][8]10,[12][13][14] Several studies have reported the utility of evaluating apparent diŠusion coe‹cient (ADC) values derived from diŠusion-weighted imaging (DWI) for diŠerentiating benign and malignant lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the enhancing patterns of focal mass lesions on dynamic study is useful in diŠeren-tiating benign and malignant lesions. [6][7][8][9][10][11] In contrast, such diŠerentiation is often di‹cult with nonmass-like enhancement because there is no standardized method of interpreting non-mass-like enhancement lesions. [6][7][8]10,[12][13][14] Several studies have reported the utility of evaluating apparent diŠusion coe‹cient (ADC) values derived from diŠusion-weighted imaging (DWI) for diŠerentiating benign and malignant lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However, as there is not yet sufficient standardisation of quantitative methods, semi-quantitative approaches have been used because they could represent a compromise between qualitative and quantitative approaches. As a general concern, DCE-MRI can achieve very high sensitivity but moderate and highly varied specificity in detecting breast cancer: reported value range from 37% up to 90% [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The vascularisation of the malignant lesions resulting from neo-vessels, that are the basis of exponential tumour growth, is one of the major reasons that dynamic features of MRI have played a crucial role in breast cancer for a decade [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations